2022
DOI: 10.3390/land11010097
|View full text |Cite
|
Sign up to set email alerts
|

How Might World Heritage Status Support the Protection of Sacred Natural Sites? An Analysis of Nomination Files, Management, and Governance Contexts

Abstract: This study provides an overview of how sacred natural sites are given recognition within the World Heritage system. It offers an analysis of the extent to which sacred natural sites that are part of nine World Heritage sites are recognised in site nomination files, management plans, and governance of these sites. The World Heritage sites are located across all continents except for Antarctica. We analysed sites in Australia, Greece, Guatemala, India, Japan, Kenya, Malaysia, New Zealand and the Russian Federati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…With increased recognition of the role of communities in the protection of some of the world's most threatened species and habitats, there are opportunities for international mechanisms to advance the ways in which they include diversity and ultimately support the custodians of nature. Verschuuren et al [14] assessed the World Heritage system and found that the cultural and spiritual significance of sacred natural sites is under-recognised, especially in natural World Heritage sites. They provide recommendations on how sacred natural sites could be better represented in the process and how to involve their custodians in the World Heritage process and in site nomination, governance, and management.…”
Section: International Designationsmentioning
confidence: 99%
“…With increased recognition of the role of communities in the protection of some of the world's most threatened species and habitats, there are opportunities for international mechanisms to advance the ways in which they include diversity and ultimately support the custodians of nature. Verschuuren et al [14] assessed the World Heritage system and found that the cultural and spiritual significance of sacred natural sites is under-recognised, especially in natural World Heritage sites. They provide recommendations on how sacred natural sites could be better represented in the process and how to involve their custodians in the World Heritage process and in site nomination, governance, and management.…”
Section: International Designationsmentioning
confidence: 99%